Strengthening Resilience of Supply with Essential Goods through Public-Private Emergency Collaborations: Challenges and Incentives - Markus Lüttenberg (KIT Scientific Publishing, 2023)
Companies can be valuable partners in delivering essential goods but must be appropriately motivated to participate in humanitarian crisis management. This work provides valuable insights into the status of humanitarian crisis management from the perspective of different stakeholders. It shows the potential of collaborative approaches, addressing the strengths and incentives of stakeholders accordingly.
Keywords: 650; incentives; collaboration; humanitarian logistics; public-private partnership; crisis management; Anreize; Kollaboration; Humanitäre Logistik; Öffentlich-Private Partnerschaft; Krisenmanagement